Aplicativo para comunicação alternativa entre a pessoa idosa e a equipe de saúde no ambiente hospitalar - Morais, Soraia Vaz de Freitas (2023)
Introduction: In the health area and more specifically in the hospital environment, communication is essential for quality and effective care, being essential to meet the will and autonomy of the elderly in decision-making regarding the course of their treatment and care. Objectives: to map in the literature the use of alternative communication in the communication process between the elderly and health professionals in the hospital environment; develop an alternative communication application between the elderly person and the health team in the hospital environment; validate the application by expert judges. Method: This is a methodological study structured in three stages: The first stage consists of investigating the scientific literature on the subject under study. At this stage, a bibliometric study was carried out, where the articles with the greatest impact and the most relevant authors on the subject were highlighted. The second step was the creation of an application for alternative communication aimed at elderly people in hospitalization. In the third stage, the application content was validated by expert judges. Results and discussion: The following were produced: 1 – A bibliometric review article “Alternative communication between the elderly and the health team in the hospital environment: a bibliometric analysis”, whose result was the mapping of the articles with the greatest impact in the scientific literature on the subject, the most relevant authors and the journals with the greatest representation on the subject. 2 – An application called VOVOZ, an alternative communication technology that aims to help the elderly in the process of communicating with the health team in the hospital environment. The application was validated by 16 judges, all health professionals, with experience in gerontology, six of them doctors and ten masters in the health area. It reached a high degree of agreement and Content Validation Index (CVI) above 0.87 in all analyzed items. Final considerations: The production of an application for alternative communication between the elderly and health professionals in the hospital environment can be very useful to improve communication and the quality of life of the elderly during the hospitalization period. The app was developed taking into account the specific needs of older people and the variety of health conditions they may have.